Characterization of UHMWPE/PEG Filament and Its Solid Form after 3D-Printing with Fused Filament Fabrication - Arifvianto, Budi; Abdullah, Muhammad J.Q.; Dharmastiti, Rini; Suyitno, Suyitno; Salim, Urip A.; Mahardika, Muslim (Journal of Fibers and Polymer Composites, 2024)
In recent decades, ultra-high molecular weight polyethylene (UHMWPE) has gained recognition and widespread utilization as an outstanding polymeric biomaterial for load-bearing components in artificial joints. Despite its promise, this material presents challenges in processing with additive manufacturing techniques. Efforts have been underway to investigate and enhance its printability with the additive manufacturing, aiming to facilitate the production of patient-specific implants. This study aims to prepare UHMWPE-based filament through extrusion and subsequently print it with fused filament fabrication (FFF) 3-dimensional (3D) printer to create a simple rectangular sheet. Characterizations by using Fourier-transform infra-red (FTIR) spectroscopy and differential scanning calorimetry (DSC) were conducted to assess the chemical compositions and thermal properties of the UHMWPE filament and its printed forms. The findings of this research demonstrate the feasibility of printing UHMWPE filament filament within the temperature range of 200 - 240 °C. Analysis of the FTIR and DSC spectra reveals no evidence of impurities introduced during the preparation and printing processes that could alter its properties.